ANALYSIS OF STUDENTS’ ABILITY IN USING ENGLISH FOR TAKING ORDER PROCEDURE IN RESTAURANT - Putra, Ida Nyoman Tri Darma (IKIP Mataram, 2018)
The aim of this study to analyze students' English speaking skills in conducting taking orders procedure in restaurants. This study is conducted in order to overcome the problems encountered by the students in speaking activities in taking orders. To measure the ability of students in speaking English in taking orders, the researchers observed the procedures that the students did not perform and measure the students’ competence of English language. Samples of this study are the fourth semester students in Hospitality courses Diploma Degree of Mataram Tourism Institute in Academic Year 2018/2019. The results of this study indicated that the level of completeness of the procedure in taking student orders in STP Mataram is in average. More than 50% students have conducted the appropriate procedure when taking orders in using English. From the result of data analysis in measuring the students’ competence in speaking English, the mean score is 78.90 with standard deviation is 12.14. From the result, it is converted and get score 3.1. The score showed that the ability of English students from 40 students in STP Mataram classified as Good Criteria.